IMPROVING STUDENTS’ VOCABULARY BY USING MIMICRY MEMORIZATION METHOD - Evelyn C. Manoppo; Herling Rares; Jenie Posumah (JELLT (Journal of English Language and Literature Teaching), 2020)
The research is about improving the students’ vocabulary by using Mimicry Memorization Method of eighth grade at SMP Berea Tondano. The purpose of this research is to find out the students’ vocabulary improvement after teach by Mimicry Memorization Method. This research is quantitative research uses pre-experimental design with one group pre-test and pos-test. This study involves 18 students. The result of this study shows that the mean score of post-test (63,61) is higher than score of pre-test (55). The result of this research shows Mimicry Memorization Method is suitable to use in help the students to improve their vocabulary. English teacher suggests to apply Mimicry Memorization Method in order to help students to improve their vocabulary. The teacher should prepare the material well to get maximum result in teaching learning process. Teacher should create the condition of the class to be fun and livelier